Factors relating to the knowledge of the elderly in fall prevention through the use of modules - Kartika, Iin Ira; Mutianingsih, Mutianingsih; Noviyanti, Lusi (Institute Of Computer Science (IOCS), 2024)
The prevalence of fall risk in the elderly ranges from 26.7% to 29.8%. The aim of this study was to analyze the effectiveness of using the module in increasing awareness among elderly families about preventing falls at home based on demographic data (age, gender, education, employment and health status). The design of this research is Quasi Experimental and one group pretest-posttest. The research sample consisted of 25 respondents whose inclusion criteria were the elderly and nursing home caregivers. The sampling method uses random sampling using primary data. Data collection was carried out by pretest, then intervention, then posttest. Statistical analysis uses the Wilcoxon test. From the results of the analysis, there is a difference in average knowledge between before (pre-test) and after (post-test) health education. The difference in the average level of knowledge about fall prevention was less than 4 respondents, 16 respondents experienced an increase in knowledge and it remained the same. knowledge of 6 respondents with a Wilcoxon test result of 0.0003 (p<0.005). From the research results, it can be concluded that there is an influence of using a module on fall prevention on the knowledge of elderly people